Release of ATP from marginal cells in the cochlea of neonatal rats can be induced by changes in extracellular and intracellular ion concentrations. - Yating Peng (Public Library of Science (PLoS), 2012)
Background Adenosine triphosphate (ATP) plays an important role in the cochlea. However, the source of ATP and the mechanism by which it is released remain unclear. This study investigates the presence and release mechanism of ATP in vitro cultured marginal cells isolated from the stria vascularis of the cochlea in neonatal rats. Methods Sprague-Dawley rats aged 1-3 days old were used for isolation, in vitro culture, and purification of marginal cells. Cultured marginal cells were verified by flow cytometry. Vesicles containing ATP in these cells were identified by fluorescence staining. The bioluminescence assay was used for determination of ATP concentration in the extracellular fluid released by marginal cells. Assays for ATP concentration were performed when the ATP metabolism of cells was influenced, and ionic concentrations in intracellular and extracellular fluid were found to change. Results Evaluation of cultured marginal cells with flow cytometry revealed the percentage of fluorescently-labeled cells as 92.9% and 81.9%, for cytokeratin and vimentin, respectively. Quinacrine staining under fluorescence microscopy revealed numerous green, star-like spots in the cytoplasm of these cells. The release of ATP from marginal cells was influenced by changes in the concentration of intracellular and extracellular ions, namely extracellular K(+) and intra- and extracellular Ca(2+). Furthermore, changes in the concentration of intracellular Ca(2+) induced by the inhibition of the phospholipase signaling pathway also influence the release of ATP from marginal cells. Conclusion We confirmed the presence and release of ATP from marginal cells of the stria vascularis. This is the first study to demonstrate that the release of ATP from such cells is associated with the state of the calcium pump, K(+) channel, and activity of enzymes related to the phosphoinositide signaling pathway, such as adenylate cyclase, phospholipase C, and phospholipase A(2).